Apistia nie rozrywa małżeństwa. Jan Chryzostom o małżonku (-nce) spoza chrześcijańskiej politei - Iluk, Jan (Vox Patrum, 2009)
Apart from a few treatises on the life of women in an extra-marital state and some short speeches about the dignity of Christian women, John Chrysostom did not engage in longer discourses about marriage. Chrysostom expressed himself most broadly on this subject in his commentary to „The First Letter to the Corinthians”. This and over a dozen other utterances by Chrysostom which I found in his writings allow us to suppose that his assessment of the value of the union between a believer and a non-believer is dictated by the realism of the epoch and not by pure dogma. Such a tone of teaching resonates with the moods of the Antioch community, which seethed with the luxuriant life of the most varied religious communities. Here, a non-believer was a partner also in marriage, hence the use of the „Pauline privilege” in order to remove such a one from a marriage would expose Christians to the accusation of a lack of tolerance at the very least. Knowing his community very well, John Chrysostom brings to the foreground the principle that a non-believer in a married couple is a problem between the non-believer and the Lord. Civil law does not make an impediment of this (such was the Roman tradition) and Canon law (the synods of the 4th century) should not make such impediments either. „Your partner’s relations with the Lord”, Chrysostom continually reminds us, „should not decide about the continuation or the dissolution of the marital union”. The „defence” of a spouse from outside the Christian politeia is also an opportunity to obtain new members of this community.